2022
DOI: 10.3390/nu14112261
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Healthy Lifestyle Habits Is a Determinant of the Effectiveness of Weight Loss among Patients Undergoing Endoscopic Bariatric Therapies

Abstract: Endoscopic bariatric therapies (EBTs) are promising strategies for the treatment of obesity. However, there is still great variability in its effectiveness in weight loss. Thus, we investigated whether adherence to healthy lifestyle habits is a significant determinant of weight loss effectiveness among patients undergoing EBTs. Additionally, the role of eating behaviors and psychological traits in the effectiveness of weight loss was studied. A cohort of 361 participants (81.4% women; age 41.8 ± 9.5 years; BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Moreover, CCAM focuses mainly on subjective outcomes such as perceived stress and happiness as health outcomes, mainly because cognitive factors are the core aspects of the model; hence, more attention should be paid to the subjective experiences of individuals [16] . In fact, some studies have widely demonstrated the effects of diet and PA on physiological indicators such as BMI and EWL% [23][24] ; therefore, our study has paid more attention to the subjective outcomes. We also focused on patients' quality of life (QOL) in this study because QOL is an important evaluation item in Bariatric Analysis and Reporting Outcome System (BAROS) [25] .…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 99%
“…Moreover, CCAM focuses mainly on subjective outcomes such as perceived stress and happiness as health outcomes, mainly because cognitive factors are the core aspects of the model; hence, more attention should be paid to the subjective experiences of individuals [16] . In fact, some studies have widely demonstrated the effects of diet and PA on physiological indicators such as BMI and EWL% [23][24] ; therefore, our study has paid more attention to the subjective outcomes. We also focused on patients' quality of life (QOL) in this study because QOL is an important evaluation item in Bariatric Analysis and Reporting Outcome System (BAROS) [25] .…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 99%
“… 16 In fact, several studies have widely demonstrated the effects of diet and PA on physiological indicators such as BMI and EWL%. 23 , 24 Therefore, this study placed greater emphasis on subjective outcomes. We also focused on patients’ quality of life (QOL) as QOL is a crucial assessment parameter in Bariatric Analysis and Reporting Outcome System (BAROS).…”
Section: Introductionmentioning
confidence: 99%